Religious Diversity and The Challenge of Multiculturalism: Contrasting Indonesia and The European Union - Muhammad Wildan (Universitas Islam Negeri Sunan Kalijaga, 2020)
As the profile of religions in the world is changing rapidly, religious diversity is becoming a more common phenomenon nowadays in almost every society. Indonesia and European Union (EU) are not an exception to be more diverse and plural societies. Although religious diversity gives such richness of culture in society, religions are known as vulnerable entities. Many social problems caused by religions brought about various conflicts and violent actions on a big scale and also numerous hostilities, discriminations, and hatred on a small scale. Many regulations have been issued to address such social tensions both in Indonesia and the EU. However, many conflicts, hostilities or discriminations are recurring in both Indonesia and EU states. Interestingly, in many cases, hostilities and discrimination even done by the apparatus of the state. The current paper is dedicated to explore how these countries deal with religious diversity and whether there are social tensions and discriminations occurred. Religion as a common phenomenon in the world should be seen more as a challenge for every country rather than a contentious threat.